'I think Irish schools need to keep doing what they're doing': Irish teachers' views on school autonomy after working in English academies. (November 2019) - Skerritt, Craig
Despite a lack of conclusive evidence connecting autonomous schools and academic success, school autonomy is regularly championed as being a way of not only improving schools but as a way of improving the quality of education in socially and economically deprived areas. This research builds on a recent paper published in Irish Educational Studies that argues that school autonomy should not be advanced in Ireland by exploring how teachers feel about features of autonomous schools. Irish teachers who have previously worked in academy schools in England, and who now teach in disadvantaged schools in Ireland, were interviewed about their experiences and how they would feel about features of autonomous schools being implemented in Ireland. The experiences the participants had in England indicate how school autonomy can be experienced in different ways – morally proper ways that engage with the broad purposes of schooling such as focusing on students and their learning, and morally improper ways that prioritise looking good on external measures at the expense of students and their learning. Overall, the participants were opposed to schools in Ireland becoming more like English academies but felt that having greater local flexibility over the curriculum in schools and offering a wider range of subjects would be beneficial, provided that it was embraced and enacted in a morally proper manner.